Identificación de lo(s) factor(es) con capacidad virulenta secretado(s) por cepas mutantes en genes arf de Mucor circinelloides - Alejandre Castañeda, Viridiana (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Arf proteins belong to the family of monomeric G proteins, which have as their main function the formation of vesicles in eukaryotic cells. Vesicles participate in vesicular traffic process, this traffic allows intra and extracellular movement of molecules for various purposes. Our group previously performed the mutation of the 4 arf genes and 2 arl genes in M. circinelloides. The cell-free culture supernatant (SS), producd in YPG rich medium, of all the arf mutants and that of the ∆arl1 (+) (-) mutant generated a greater virulence rate with respect to the wildtype strain, with the ∆arf3 mutant SS being the one that generated the highest level of virulence. In part, it was possible to explain that the molecule (s) secreted by the mutants ∆arf3 and ∆arl1 (+) / (-) is related to a protein nature. In this work, the YNB culture medium was used, which has as its only nitrogen source ammonium sulfate, which, unlike YPG, does not interfere with the presence of peptone derived from gelatin peptone. The SS produced in YNB medium from mutant ∆arf3 y ∆arl1(+)/(-) strains maintained the virulent activity, in addition to finding that the virulent factor (s) are susceptible to the action of proteases, moreover to being accumulated (s) with respect to the growth of M. circinelloides. The separation of the components secreted to the culture medium by the use of molecular exclusion membranes showed that the molecular weight of the virulence factor is less than 3 kDa. On the other hand, the virulence capacity of the virulent factor (s) is maintained even after being subjected to 97°C for 30 minutes. Increased siderophore presence was observed in the ∆arf3 and ∆arl1(+)/(-) mutant strains.

Las proteinas Arf pertenecen a la familia de proteinas G monoméricas, las cuales tienen como función principal la formación de vesículas en las células eucarioticas. Las vesículas participan en el tráfico vesicular, este tráfico permite el movimiento intra y extracelular de moléculas con diversos fines. Nuestro grupo realizó previamente la mutación de los 4 genes arf y 2 genes arl en M. circinelloides. El sobrenadante de cultivo (medio rico YPG) de todas las mutantes arf y el de la mutante arl1(+)(-) generó una mayor virulencia respecto a la cepa silvestre, siendo el sobrenadante de la mutante ∆arf3 el que generó el mayor nivel de virulencia. En parte se logró explicar que esta relacionada a una naturaleza protéica la(s) molécula(s) secretada(s) por parte de las mutantes ∆arf3 y ∆arl1(+)/(-). En este trabajo se usó el medio de cultivo YNB, el cual posee como única fuente de nitrógeno sulfato de amonio, que a diferencia del YPG, no interfiere con la presencia de péptidos derivados de la peptona de gelatina. El sobrenadante producido en medio YNB mantuvo la actividad virulenta, además de encontrar que el(los) factor(es) virulento(s) son suceptibles a la acción de proteasas, además de ser acumulado(s) respecto al crecimiento de M. circinelloides. La separación de los componentes secretados al medio de cultivo mediante el uso de membranas de exclusión molecular demostró que el peso molecular de dicho factor de virulencia es menor de 3 kDa. Por otra parte, la capacidad de virulencia de dicho(s) factor(es) se mantiene incluso después de ser sometida a 97ºC durante 30 minutos. Se observó una mayor actividad de sideróforo en las mutantes ∆arf3 y ∆arl1(+)/(-).
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2020-0348; Mucormicosis; Virulencia; Vesículas secretables; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3979